The Use Combined Adsorbant to Extend the Storing Period of Cavendish Banana - Suryatmi Retno Dumadi (Jurnal Teknologi dan Industri Pangan, 2001)
Post harvest damage of horticulture commodity in Indonesia has reached 30 to 40%. This research is aimed at extending the storing period of cavendish banana in order to extend the market range, while still enabling to maintain the quality of fresh preserved banana as required by consumers. One of the ways to do so is by using combines adsorbant as to control the air of the fruit surrounding.The type of adsorbant used is as follows : 1,2 and 3% of KMn04 ; 0,5, 1 and 1,5% of iron powder, and 3% of active carbon. The experiment was conducted in completed randomized design, by 10 factors of combined and concentrate adsorbant, and by 6 factors of storing time. The parameters being analyzed includes texture intensity, starch rate, total acid rate, total glucose rate, water rate and reduced glucose rate.The statistics test results of 10 treatments of combines adsorbant KMn04, iron powder, active carbon which were(1%, 0,5%, 3%), (1%, 1%, 3%), (1%, 1,5%,3%), (2%, 0,5%, 3%), (2%, 1%, 3%), (2%, 1.5%, 3%) (3%, 0,5%, 3%), (3%, 1%, 3%) ( 3%, 1,5%, 3%), suggested that the combined adsorbant (2%, 1,5%, 3%) at 15Ã‚Â°C storing temperature is the best. This treatment is the best because it has the highest substances rate up to 72.36% db; relatively small texture change, total acid rate, total glucose rate, water rate and the lowest reduced glucose rate of 3.531% db which is more likely to extend the storing period of cavendish banana for approximately six weeks.Key Words : horticulture, cavendish, adsorbant, texture, storing period.